Danish method study on cervical screening in women offered HPV vaccination as girls (Trial23): a study protocol - Thamsborg, Lise Holst (BMJ Open, 2018)
INTRODUCTION: The first birth cohorts of women offered human papillomavirus (HPV) vaccination as girls are now entering cervical screening. However, there is no international consensus on how to screen HPV vaccinated women. These women are better protected against cervical cancer and could therefore be offered less intensive screening. Primary HPV testing is more sensitive than cytology, allowing for a longer screening interval. The aim of Trial23 is to investigate if primary HPV testing with cytology triage of HPV positive samples is a reasonable screening scheme for women offered HPV vaccination as girls. METHODS: Trial23 is a method study embedded in the existing cervical screening programme in four out of five Danish regions. Without affecting the screening programme, women born in 1994 are randomised to present screening with liquid-based cytology every third year (present programme arm) or present screening plus an HPV test (HPV arm). The study started 1 February 2017 and will run over three screening rounds corresponding to 7–8 years. ANALYSES: The primary endpoint is cervical intraepithelial neoplasia grade 3 or above. The trial is undertaken as a non-inferiority study including intention-to-treat and per-protocol analyses. The potential effect of primary HPV screening with a 6-year interval will be calculated from the observed data. ETHICS AND DISSEMINATION: The study protocol has been submitted to the ethical committee and deemed a method study. All women are screened according to routine guidelines. The study will contribute new evidence on the future screening of HPV vaccinated birth cohorts of women. All results will be published in open-access journal. TRIAL REGISTRATION: NCT03049553; Pre-results.